Determinants Of Factors Affecting The Implementation Of The HPV Vaccination In Women Of Childbearing Age - bherty, chanda paramitha; Prihartanti, Niken Grah; Faizah, Nur Laila; Aliza, Ana Dyah (Jurnal Ilmu Kesehatan, 2022)
Abstract: “Cases of cervical cancer in women of childbearing age are caused by infection with the human papilloma virus. Efforts to prevent cervical cancer in women of childbearing age are influenced by the understanding of HPV knowledge. The method of this research is cross sectional, the population taken in this study are women of childbearing age in Jombang district with a total of 71 respondents. The technique used in sampling is incidental sampling. The inclusion criteria for sampling are as follows: Women of childbearing age who have internet access, Women of childbearing age who are willing to be respondents. This research was conducted online using google-form. Researchers collected data using a questionnaire sheet to assess the age, education, occupation, income and knowledge of women of childbearing age. Analysis using Pearson bivariate correlation data analysis. The results showed that women of childbearing age had very good knowledge of HPV vaccination (49.3%). But it is not statistically significant on the factors of age, occupation, education and income. Keywords : Knowledge, HPV(Human Papilloma Virus), Women, Childbearing Age